Lexical Bundles in Reading Passages of English Textbook for Senior High School: A Comparative Study Between Three Textbooks of Different Grades - Ritanti Lasmita; Alamsyah Harahap; Safnil Arsyad (English Education Study Program Faculty of Teacher Training and Education, 2023)
This study discusses lexical bundles in reading passages in English textbooks for senior high school. This study has two objectives, the first is to find out lexical bundles three-word and four-word are found in reading passages of English Textbook for senior high school for X, XI, and XII grade. Second, To find of lexical Category types found in reading passages of English Textbook for senior high school entitled ”Bahasa Inggris” for X, XI, and XII grade. In addition, this study used theory from Biber. According to Biber, the categories of lexical bundles are noun phrase, verb phrase and prepositional phrase. This study uses a quantitative descriptive method used reading passages in an English textbook for senior high school entitled